Cof magnetic nanoparticle solid phase microextraction material, preparation method and application thereof

CN122974284APending Publication Date: 2026-10-27南昌大学第一附属医院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611194515.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,目前关于将基于三(4-甲酰苯基)胺和富氮三嗪单元的COF材料应用于磁固相萃取水环境中NSAIDs的研究仍较少

Benefits of technology

本发明在磁性纳米颗粒Fe3O4表面修饰COF TAPT-TFA从而制备得到COF TAPT-TFA磁性纳米颗粒固相微萃取材料。具体而言,本发明在磁性纳米颗粒Fe3O4表面修饰的COFTAPT-TFA是一种以1,3,5-三(4-氨基苯基)三嗪(TAPT)和三(4-甲酰苯基)胺(TFA)为单体的富氮型多孔材料。与现有技术相比,本发明具有以下显著优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a COF magnetic nanoparticle solid-phase microextraction material and a preparation method and application thereof, and relates to the technical field of material preparation and application. First, the hydrothermal synthesis method is used to generate magnetic nanoparticles Fe3O4 by taking FeCl3.6H2O as an iron source. Then, a nitrogen-rich covalent organic framework is modified on the surface of the magnetic nanoparticles Fe3O4 by taking TAPT and TFA as monomers through a solvothermal method, so that a cross-linked magnetic extraction material with excellent dispersity is obtained. The COF material of the application contains a large number of triazine rings and tertiary amine structures in the framework, has extremely high nitrogen content and rich adsorption active sites, can significantly enhance the specific adsorption capacity of non-steroidal anti-inflammatory drugs through multiple hydrogen bond, pi-pi stacking and acid-base interaction mechanisms, and can improve the enrichment multiple and extraction selectivity, so as to meet the demand of detecting low-concentration target objects in water environmental samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials preparation and application technology, specifically to COF magnetic nanoparticle solid-phase microextraction materials, their preparation methods, and applications. Background Technology

[0002] With rapid industrialization and urbanization, large quantities of organic chemicals are widely used and discharged into aquatic environments, making water pollution a globally significant environmental problem. Non-steroidal anti-inflammatory drugs (NSAIDs) are a class of anti-inflammatory drugs without steroidal structures that work by targeting cyclooxygenase (COX). Clinically, they are widely used to relieve symptoms of osteoarthritis, rheumatoid arthritis, various fevers, and various pain symptoms. As a widely used class of pharmaceutically active compounds, NSAIDs are commonly detected in environmental water bodies, posing a potential threat to ecosystems and human health. Therefore, establishing accurate and reliable methods for detecting trace NSAIDs in aquatic environments is crucial.

[0003] Currently, the concentration of NSAIDs in environmental water samples is typically extremely low and the matrix is ​​complex, requiring sample pretreatment before detection. Existing pretreatment methods include liquid-liquid extraction, solid-phase extraction, and liquid-phase microextraction. However, these methods generally suffer from drawbacks such as time-consuming steps, insufficient selectivity, significant matrix effects, and high consumption of organic solvents. Therefore, developing efficient, sensitive, and environmentally friendly pretreatment methods is of great significance. Magnetic solid-phase extraction (MSPE) offers advantages such as simple operation, environmental friendliness, high extraction efficiency, and easy material recovery. Fe3O4-based magnetic nanoparticles, due to their ease of functionalization to improve selectivity for target analytes, have been widely used in the analysis of complex matrices such as food, environmental samples, and biological systems. In MSPE, the extraction efficiency largely depends on the surface modification coating. Therefore, developing coating materials with high extraction rates and enrichment efficiencies is crucial for the efficient enrichment of NSAIDs in complex matrices. Covalent organic frameworks (COFs) are a class of crystalline organic porous materials with permanent porosity and highly ordered structures.

[0004] In recent years, COF materials have shown broad application prospects in the field of adsorption separation due to their high specific surface area, tunable pore size, and abundant functionalization sites. However, there are still few studies on applying COF materials based on tris(4-formylphenyl)amine and nitrogen-rich triazine units to magnetic solid-phase extraction of NSAIDs in water environments. Summary of the Invention

[0005] The purpose of this invention is to at least solve one of the technical problems existing in the prior art, and to provide COF magnetic nanoparticle solid-phase microextraction materials, their preparation methods and applications.

[0006] The technical solution of the present invention is as follows: The method for preparing COF magnetic nanoparticle solid-phase microextraction material involves using FeCl3•6H2O as the iron source and generating magnetic nanoparticles Fe3O4 under alkaline conditions via hydrothermal synthesis. Then, using 1,3,5-tris(4-aminophenyl)triazine and tris(4-formylphenyl)amine as monomers, COF TAPT-TFA is modified onto the surface of the Fe3O4 magnetic nanoparticles via a solvothermal method to obtain the solid-phase microextraction material.

[0007] Preferably, the preparation method of the magnetic nanoparticles Fe3O4 includes the following specific steps: mixing ethylene glycol, anhydrous sodium acetate, sodium poly(4-styrenesulfonic acid-copoly-maleic acid) salt and FeCl3•6H2O to obtain a mixed solution; reacting the mixed solution at 150-200℃ for 6-12h; after the reaction is completed, cooling to room temperature, separating the product, washing and drying the product to obtain magnetic nanoparticles Fe3O4.

[0008] Preferably, the molar ratio of FeCl3•6H2O to sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) is 1:0.5-4; the molar ratio of FeCl3•6H2O to anhydrous sodium acetate is 1:8-20; and the addition ratio of FeCl3•6H2O to ethylene glycol is 0.4-0.6g:10-50mL.

[0009] Preferably, the preparation method of the solid-phase microextraction material includes the following specific steps: mixing 1,3,5-tris(4-aminophenyl)triazine, tris(4-formylphenyl)amine and the magnetic nanoparticles Fe3O4, then adding n-butanol, water and glacial acetic acid, reacting at 60-80℃ for 14-18h, after the reaction is completed, separating the product, washing and drying the product to obtain the solid-phase microextraction material.

[0010] Preferably, the molar ratio of 1,3,5-tris(4-aminophenyl)triazine to tris(4-formylphenyl)amine is 1:1, the mass ratio of 1,3,5-tris(4-aminophenyl)triazine to magnetic nanoparticles Fe3O4 is 25-50:20-50, and the addition ratio of 1,3,5-tris(4-aminophenyl)triazine, n-butanol, water and glacial acetic acid is 25-50 mg:0.5-2.5 mL:0.1-0.4 mL:0.2-0.8 mL.

[0011] This invention also discloses COF magnetic nanoparticle solid-phase microextraction materials, which are prepared using any of the preparation methods described above.

[0012] This invention also discloses the application of COF magnetic nanoparticle solid-phase microextraction material in the enrichment of trace nonsteroidal anti-inflammatory drug pollutants.

[0013] Preferably, the nonsteroidal anti-inflammatory drug contaminant includes at least one of diclofenac sodium, naproxen, and ibuprofen.

[0014] This invention also discloses a method for detecting nonsteroidal anti-inflammatory drug (NSAID) contaminants, comprising the following steps: mixing COF magnetic nanoparticle solid-phase microextraction material with the test solution to extract and enrich NSAID contaminants in the test solution; after extraction and enrichment, separating the COF magnetic nanoparticle solid-phase microextraction material, discarding the water sample, adding methanol and 0.1 M sodium hydroxide as eluent for elution, collecting the eluent after elution, and filtering the eluent through a filter membrane and detecting it by a high-performance liquid chromatography-diode array detector.

[0015] Preferably, the extraction and enrichment conditions include: an extraction and enrichment time of 5-30 min, a pH of 4-9, and an extraction material dosage of 0.25-2.0 mg COF magnetic nanoparticle solid-phase microextraction material per 4 mL of test solution; an elution time of 5-30 min; separation using a 200 mm × 2.1 mm, 1.9 µm C18 column, a flow rate of 0.3 mL / min, and an injection volume of 20 µL.

[0016] This invention has at least one of the following beneficial effects: This invention modifies the surface of Fe3O4 magnetic nanoparticles with COF TAPT-TFA to prepare COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material. Specifically, the COF TAPT-TFA modified on the surface of Fe3O4 magnetic nanoparticles is a nitrogen-rich porous material with 1,3,5-tris(4-aminophenyl)triazine (TAPT) and tris(4-formylphenyl)amine (TFA) as monomers. Compared with the prior art, this invention has the following significant advantages: (1) The nitrogen-rich skeleton provides multiple forces: The COF structure contains a high density of triazine ring nitrogen atoms and tertiary amine nitrogen atoms, which on the one hand provides abundant electronegative sites, which can form strong hydrogen bonds (OH···N) and acid-base / electrostatic interactions with the carboxyl and phenolic hydroxyl groups in nonsteroidal anti-inflammatory drug molecules; on the other hand, the nitrogen-rich fused ring structure enhances the local charge density of the COF skeleton, significantly improving the π-π stacking interaction with the aromatic rings of NSAIDs, thereby achieving efficient and selective capture of the target.

[0017] (2) Excellent magnetic response performance: The prepared Fe3O4@COF TAPT-TFA composite material has both the magnetic response characteristics of Fe3O4 and the high specific surface area and abundant adsorption sites of COF. It is easy to operate and environmentally friendly.

[0018] (3) Good reusability: The material has good reusability and can be recycled multiple times while maintaining high extraction efficiency. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the synthesis and extraction process of the Fe3O4@COF TAPT-TFA magnetic solid phase extraction material described in this invention.

[0020] Figure 2 Photographs of the synthetic materials of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA of this invention.

[0021] Figure 3 The infrared spectra of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA of this invention are shown.

[0022] Figure 4 Thermogravimetric analysis (TGA) diagrams of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA of this invention are shown.

[0023] Figure 5 The X-ray photoelectron spectroscopy characterization diagrams of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA of the present invention are shown.

[0024] Figure 6 The nitrogen adsorption desorption curves and pore size distributions of COF TAPT-TFA and Fe3O4@COF TAPT-TFA of this invention are shown.

[0025] Figure 7 The X-ray diffraction characterization patterns of Fe3O4 and Fe3O4@COF TAPT-TFA of the present invention are shown.

[0026] Figure 8 The hysteresis curves of Fe3O4 and Fe3O4@COF TAPT-TFA of this invention are shown.

[0027] Figure 9The figure shows the effect of extraction conditions on the extraction efficiency of the Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material described in this invention. In the figure, (a) represents the type of elution solvent, (b) represents the elution time, (c) represents the salt concentration of the extraction solution, (d) represents the adsorbent dosage, (e) represents the pH value of the extraction solution, and (f) represents the extraction time.

[0028] Figure 10 This is a repeatability graph of the Fe3O4@COF TAPT-TFA described in this invention.

[0029] Figure 11 This is a comparison chart showing the detection effects of Fe3O4@COF TAPT-TFA magnetic solid phase extraction material in Example 2 of the present invention and non-nitrogen-rich COF magnetic solid phase extraction material in the comparative example on nonsteroidal anti-inflammatory drug compounds. Detailed Implementation

[0030] This invention provides a COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material, its preparation method, and its application. Specifically, the first objective of this invention is to provide a nitrogen-rich covalent organic framework material based on 1,3,5-tris(4-aminophenyl)triazine (TAPT) and tris(4-formylphenyl)amine (TFA); the second objective is to provide a magnetic solid-phase extraction material; and the third objective is to provide an application of the magnetic solid-phase extraction material in the detection of nonsteroidal anti-inflammatory drug compounds.

[0031] This invention first utilizes a hydrothermal synthesis method, using FeCl3•6H2O as the iron source. Under high temperature and alkaline conditions, ferric ions are partially reduced to ferrous ions by ethylene glycol, thereby generating magnetic nanoparticles Fe3O4. Subsequently, using 1,3,5-tris(4-aminophenyl)triazine (TAPT) and tris(4-formylphenyl)amine (TFA) as monomers, COFTAPT-TFA is modified on the surface of Fe3O4 via a solvothermal method to obtain a magnetic extraction material with excellent dispersibility.

[0032] The COF TAPT-TFA structure of this invention has a significant "nitrogen-rich" advantage, specifically manifested in: (1) The COF framework contains a high density of triazine ring units and tertiary amine centers, with extremely high nitrogen content, providing abundant electronegative sites and lone pairs of electrons; (2) The high nitrogen content endows the COF skeleton with excellent electron-donating ability, which can form strong hydrogen bond interactions (OH···N) with carboxyl (-COOH), hydroxyl (-OH) and other groups in nonsteroidal anti-inflammatory drug molecules. (3) The triazine ring and the benzene ring form a huge π-π conjugated system, which generates a strong π-π stacking effect with the aromatic ring in the NSAID molecule; (4) The basic nitrogen sites in the nitrogen-rich framework can interact with the acidic groups of NSAIDs through acid-base / electrostatic interactions, thereby achieving highly selective recognition and efficient capture of anti-inflammatory drug molecules in complex water sample matrices; (5) The introduction of nitrogen atoms improves the hydrophilicity / hydrophobicity balance of the COF framework, which is beneficial for uniform dispersion in the aqueous phase and full contact with the target substance.

[0033] The aforementioned multiple synergistic mechanisms enable the COF TAPT-TFA material of this invention to exhibit adsorption capacity and enrichment factor far superior to traditional nonfunctionalized COF materials for nonsteroidal anti-inflammatory drug compounds, thus meeting the requirements for detecting low concentrations of target compounds in aquatic environmental samples.

[0034] The technical solution of the present invention is as follows (for reference) Figure 1 ): In a first aspect, the present invention provides a method for preparing COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material, comprising the following steps: using a hydrothermal synthesis method, FeCl3•6H2O is used as an iron source to partially reduce ferric ions to ferrous ions under high temperature and alkaline conditions to generate magnetic nanoparticles Fe3O4; using 1,3,5-tris(4-aminophenyl)triazine and tris(4-formylphenyl)amine as monomers, COF TAPT-TFA is modified on the surface of the magnetic nanoparticles Fe3O4 by a solvothermal method to obtain COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material.

[0035] Optionally, the preparation method of the magnetic Fe3O4 nanoparticles includes the following specific steps: Ethylene glycol, anhydrous sodium acetate, sodium poly(4-styrenesulfonic acid-copoly-maleic acid) salt and FeCl3•6H2O were mixed to obtain a mixture. The mixture was reacted at 150-200℃ for 6-12 h. After the reaction was completed, the mixture was cooled to room temperature, the product was separated, and the product was washed and dried to obtain magnetic nanoparticles Fe3O4.

[0036] Optionally, the molar ratio of FeCl3•6H2O to sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) is 1:0.5-4, more preferably 1:1; the molar ratio of FeCl3•6H2O to anhydrous sodium acetate is 1:8-20, more preferably 1:13; and the addition ratio of FeCl3•6H2O to ethylene glycol is 0.4-0.6 g:10-50 mL, more preferably 0.54 g:20 mL.

[0037] Optionally, the preparation method of COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material includes the following specific steps: 1,3,5-tris(4-aminophenyl)triazine, tris(4-formylphenyl)amine and the magnetic nanoparticles Fe3O4 are mixed, and then n-butanol, water and glacial acetic acid are added. The mixture is reacted at 60-80℃ for 14-18 h. After the reaction is completed, the product is separated, washed and dried to obtain COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material.

[0038] Optionally, the molar ratio of 1,3,5-tris(4-aminophenyl)triazine to tris(4-formylphenyl)amine is 1:1, the mass ratio of 1,3,5-tris(4-aminophenyl)triazine to magnetic nanoparticles Fe3O4 is 25-50:20-50, and the addition ratio of 1,3,5-tris(4-aminophenyl)triazine, n-butanol, water and glacial acetic acid is 25-50 mg:0.5-2.5 mL:0.1-0.4 mL:0.2-0.8 mL.

[0039] Optionally, a method for preparing a COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material includes the following steps: Step 1: Prepare Fe3O4 magnetic nanoparticles; Sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) was placed in ethylene glycol and stirred for 30 min to disperse it evenly. FeCl3•6H2O and anhydrous sodium acetate were added to the above solution and stirred for 30 min. The resulting mixed solution was transferred to a reaction vessel and reacted at 150-200℃ for 6-12 h. After the reaction was completed, the mixture was cooled to room temperature and the product was separated by a magnet. The product was washed 3-5 times with deionized water and ethanol, and then vacuum dried at 50℃ for 8-12 h to obtain Fe3O4 magnetic nanoparticles with uniform particle size distribution.

[0040] Step 2: Prepare Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material; 1,3,5-tris(4-aminophenyl)triazine, tris(4-formylphenyl)amine, and Fe3O4 particles were added to a pressure-resistant bottle in a certain proportion, followed by the addition of n-butanol, water, and glacial acetic acid. The mixture was reacted at 60-80℃ for 14-18 hours. After the reaction was completed, the mixture was separated by an external magnetic field and washed 3-5 times with methanol and water, respectively, to obtain Fe3O4@COF TAPT-TFA.

[0041] Secondly, the present invention provides a COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material, which is obtained by the preparation method described above.

[0042] This invention modifies the surface of magnetic nanoparticles Fe3O4 with COF TAPT-TFA. COF is a porous material containing a high-density triazine ring and a triphenylamine core. It has nitrogen-rich properties, a large conjugated system and multiple recognition sites, and can efficiently adsorb nonsteroidal anti-inflammatory drug compounds through mechanisms such as π-π stacking, hydrophobic interaction, hydrogen bonding and acid-base interaction.

[0043] Thirdly, the present invention provides the application of the COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material in the enrichment of trace non-steroidal anti-inflammatory drug pollutants.

[0044] The magnetic nanoparticle coating utilizes the COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material described in this invention. In practical applications, the Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material can be used to enrich and extract trace amounts of nonsteroidal anti-inflammatory drugs (including diclofenac sodium, ibuprofen, and naproxen) from the aqueous environment. The enrichment and extraction conditions are: extraction time 5-30 min, pH 4-9, and extraction material dosage of 0.25-2.0 mg per 4 mL of water sample. More preferably, the extraction time is 10 min; the extraction pH is 6; and the extraction material dosage is 1.0 mg per 4 mL of water sample.

[0045] Fourthly, this invention provides the application of the COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material combined with HPLC-DAD in the detection of nonsteroidal anti-inflammatory drug contaminants.

[0046] This invention uses COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material to extract and enrich nonsteroidal anti-inflammatory drug pollutants. After enrichment and extraction, the eluent is eluted with an elution solvent, and then the eluent is detected by HPLC-DAD, which allows for the detection of nonsteroidal anti-inflammatory drug pollutants.

[0047] Optionally, after enrichment extraction, elution is performed with an elution solvent for 5-30 minutes, wherein the elution solvent is methanol / 0.1 M sodium hydroxide (v / v=9:1). More preferably, the elution time is 10 minutes.

[0048] Optionally, after elution, the eluent is detected by HPLC-DAD. The HPLC conditions are as follows: C18 column parameters are 200 mm × 2.1 mm and 1.9 µm; mobile phase A is a 0.1% formic acid aqueous solution and mobile phase B is methanol. Isocratic elution is used with a flow rate of 0.3 mL / min and an injection volume of 20 µL.

[0049] Fifthly, the present invention provides a method for detecting nonsteroidal anti-inflammatory drug contaminants, comprising the following steps: The COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material was mixed with the test solution to extract and enrich non-steroidal anti-inflammatory drug contaminants in the test solution. After extraction and enrichment, COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material was separated, water sample was discarded, methanol was added for elution, and the eluent was collected after elution. The eluent was filtered through a filter membrane and then detected by high performance liquid chromatography-diode array detector. Mobile phase A was an aqueous solution of formic acid with a volume fraction of 0.1%; mobile phase B was methanol, and isocratic elution was used.

[0050] Optionally, the extraction and enrichment conditions include: an extraction and enrichment time of 5-30 min, a pH of 4-9, and an extraction material dosage of 0.5-2.0 mg COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material per 4 mL of the test solution; an elution time of 5-30 min; separation using a 200 mm × 2.1 mm, 1.9 µm C18 column, a flow rate of 0.3 mL / min, and an injection volume of 20 µL.

[0051] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and are not intended to limit the invention.

[0052] The raw materials used in the following examples are as follows: Ferric chloride hexahydrate (FeCl3•6H2O, ≥99%), anhydrous sodium acetate (CH3COONa, ≥99%), ethylene glycol (EG, ≥99.5%), sodium poly(4-styrenesulfonic acid-copoly-maleic acid) (PSSMA), 1,3,5-tris(4-aminophenyl)triazine (TAPT, 97%), and tris(4-formylphenyl)amine (TFA, 97%) were all purchased from Aladdin Chemical Co., Ltd. (Shanghai, China). Glacial acetic acid, n-butanol, methanol (HPLC grade), and acetonitrile (HPLC grade) were purchased from Sinopharm Chemical Reagent Co., Ltd. (Beijing, China). Diclofenac sodium (DCF, ≥98%), ibuprofen (IBP, ≥98%), and naproxen (NAP, ≥98%) were purchased from Maclean Biochemical Technology Co., Ltd.

[0053] Example 1 This embodiment provides a method for synthesizing COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material. In this embodiment, the COF TAPT-TFA magnetic nanoparticle solid-phase microextraction material is specifically Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material.

[0054] The synthesis method of Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material in this embodiment includes the following steps: (1) Sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) salt (1g) was placed in 40mL of ethylene glycol and stirred for 1h to disperse it evenly, thus obtaining a sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) salt solution; then, FeCl3•6H2O (1.08g) and anhydrous sodium acetate (5.0g) were added to the above sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) salt solution and stirred for 0.5h. The resulting mixed solution was transferred to a reaction vessel and reacted at 180℃ for 12h. After cooling to room temperature, the mixture was washed three times with deionized water and three times with ethanol. The mixture was collected under an external magnetic field, separated, and dried at 60℃ for 12h to obtain black-brown Fe3O4 magnetic nanoparticles.

[0055] (2) Add 1,3,5-tris(4-aminophenyl)triazine (TAPT, 42.4 mg), tris(4-formylphenyl)amine (TFA, 39.4 mg), black-brown Fe3O4 magnetic nanoparticles (40 mg), n-butanol (2012 µL), water (300 µL), and glacial acetic acid (18 M, 700 µL) to a pressure-resistant bottle. Sonicate for 5 min, react at 70 °C with magnetic stirring for 16 h, wash three times with anhydrous methanol, separate with an external magnetic field, and dry at 80 °C for 12 h to obtain Fe3O4@COF TAPT-TFA magnetic solid phase extraction material.

[0056] (3) The same steps as in (2) were followed to synthesize the individual COF TAPT-TFA material, but without the addition of Fe3O4 nanoparticles: 1,3,5-tris(4-aminophenyl)triazine (TAPT, 42.4 mg), tris(4-formylphenyl)amine (TFA, 39.4 mg), n-butanol (2012 µL), water (300 µL), and glacial acetic acid (18 M, 700 µL) were added to a pressure-resistant bottle. The mixture was sonicated for 5 min, and reacted under magnetic stirring at 70 °C for 16 h. After centrifugation, the mixture was washed three times with anhydrous methanol and dried at 80 °C for 12 h to obtain the COF TAPT-TFA material.

[0057] Physical images of COF TAPT-TFA prepared in Example 1 (3), Fe3O4 prepared in Example 1 (1), and Fe3O4@COF TAPT-TFA prepared in Example 1 (2) are shown below. Figure 2 The COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA magnetic solid-phase extraction materials prepared in Example 1 were characterized, and the results are as follows: 1. The FT-IR spectra of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA are as follows: Figure 3As shown, the appearance of the C=N characteristic peak in COF TAPT-TFA indicates that COF TAPT-TFA was successfully synthesized via the Schiff base reaction. Fe3O4@COF TAPT-TFA at 585 cm⁻¹... -1 The characteristic peak of Fe-O-Fe bond appears at 1626 cm⁻¹. -1 The presence of a characteristic absorption peak at C=N confirms the successful preparation of the Fe3O4@COF TAPT-TFA composite material.

[0058] 2. Thermogravimetric analysis (TGA) results of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA are shown in [the table below]. Figure 4 .Depend on Figure 4 It was found that Fe3O4 exhibited only about 28% mass loss in the 30-800℃ range, attributed to the removal of adsorbed water and hydroxyl groups from the nanoparticle surface. No significant mass loss was observed in COF TAPT-TFA below 500℃, indicating that its framework structure remained stable within this temperature range; however, significant mass loss occurred in the 500-800℃ range, attributed to the thermal breakage of covalent bonds in the COF framework and the decomposition of organic components. The Fe3O4@COF TAPT-TFA composite material exhibited the thermogravimetric characteristics of both Fe3O4 and COF TAPT-TFA. This good thermal stability ensured the structural integrity and stable extraction performance of the composite material during extraction, elution, and regeneration.

[0059] 3. X-ray photoelectron spectroscopy results of COF TAPT-TFA, Fe3O4, and Fe3O4@COF TAPT-TFA are shown in [reference needed]. Figure 5 .Depend on Figure 5 It can be seen that, compared with the XPS full spectrum of Fe3O4 and COF TAPT-TFA alone, the Fe3O4@COF TAPT-TFA composite material simultaneously exhibits characteristic energy spectrum peaks of Fe 2p, O 1s, N 1s and C 1s, confirming the presence of the corresponding elements in the Fe3O4@COF TAPT-TFA composite material and indicating the successful preparation of the extraction material.

[0060] 4. The nitrogen adsorption and desorption experimental results of COF TAPT-TFA and Fe3O4@COF TAPT-TFA are shown in [the table below]. Figure 6 . Figure 6 The BET surface area of ​​COF TAPT-TFA was found to be 1316.8 m². 2 / g, pore volume is 0.61cm³ 3 / g, with an average pore size of 3.97nm, and a BET surface area of ​​892.5m² for the Fe3O4@COF TAPT-TFA composite material. 2 / g, pore volume is 0.42cm³ 3 / g, with an average pore size of 4.55nm.

[0061] 5. X-ray diffraction results of COF TAPT-TFA and Fe3O4@COF TAPT-TFA are shown in [Figure number missing]. Figure 7 The main characteristic peaks of Fe3O4 are located at 30.3°, 35.6°, 43.2°, 57.3°, and 62.9°, which are consistent with the (220), (311), (400), (511), and (440) crystal planes in the standard pure phase of Fe3O4. New characteristic diffraction peaks appeared in the composite material modified with COF TAPT-TFA, indicating the successful preparation of the composite extraction material.

[0062] 6. The magnetization curves of Fe3O4 and Fe3O4@COF TAPT-TFA are shown in [reference needed]. Figure 8 Magnetization curve: The saturation magnetization of Fe3O4@COF TAPT-TFA is about 15 emu / g, which is lower than the magnetic strength of Fe3O4 material (54 emu / g). This is related to the COF encapsulation, but it still has good magnetic response performance.

[0063] In summary, the successful preparation of Fe3O4@COF TAPT-TFA composite material lays the foundation for its adsorption and enrichment of nonsteroidal anti-inflammatory drugs.

[0064] Comparative Example 1 In Example 1, the COF synthesis ligand tris(4-formylphenyl)amine (TFA) was replaced with tris(4-aldehydephenyl)methane, and 1,3,5-tris(4-aminophenyl)triazine (TAPT) was replaced with a conventional nitrogen-free monomer (1,3,5-tris(4-aminophenyl)benzene). Non-nitrogen-rich conventional Fe3O4@COF TAPB-TFP magnetic solid-phase extraction material was prepared by the same method.

[0065] Example 2 This embodiment provides a method for detecting trace nonsteroidal anti-inflammatory drug (NSAID) compounds in an aquatic environment. Specifically, the Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material synthesized in Example 1 is applied to the enrichment and detection of trace NSAID compounds in an aquatic environment. The NSAID compounds detected in this embodiment include, but are not limited to, diclofenac (DCF), ibuprofen (IBP), and naproxen (NAP).

[0066] I. This invention, based on Fe3O4@COF TAPT-TFA composite nanomaterials and HPLC-DAD technology, constructs a method for detecting trace nonsteroidal anti-inflammatory drug compounds in the aquatic environment. The method includes the following detection steps: 1. Sample preparation: Take 4 mL of actual water sample or standard working solution containing nonsteroidal anti-inflammatory drug compounds, add 0.25-2.0 mg of the black-brown powdered Fe3O4@COF TAPT-TFA composite nanomaterial prepared in Example 1, and shake at 250 rpm for 5-30 min at room temperature for adsorption.

[0067] 2. Separation, Elution, and Detection: Fe3O4@COF TAPT-TFA composite material was adsorbed using a magnet. 500µL of elution solvent was added, and elution was carried out for 5-30 min. The eluent was detected using HPLC-DAD. Phase A was an aqueous solution of formic acid with a volume fraction of 0.1%, and Phase B was 100% methanol. Separation was performed using a 200 mm × 2.1 mm, 1.9µm C18 column with isocratic elution at a flow rate of 0.3 mL / min and an injection volume of 20µL. The type and concentration of pollutants were determined by DAD detection of peak time and peak area. The extraction conditions were investigated, specifically the effects of adsorbent dosage (0.25-2.0 mg), extraction time (5-30 min), extract pH (4-9), elution solvent type (methanol, acetonitrile, ethanol, 0.1 M sodium hydroxide (NaOH), methanol / 0.1 M NaOH (v / v=9:1)), NaCl salt concentration (0-50 mmol / L), and elution time (5-30 min) on the extraction results. The experimental results are as follows: Figure 9 As shown. Based on the experimental results, the extraction time was ultimately selected as 10 min, the adsorption dose as 1.0 mg, the pH value of the extraction solution as 6, the salt concentration as 0 mmol / L, the elution solvent as methanol / 0.1 M NaOH (v / v=9:1), and the elution time as 10 min.

[0068] 3. Method validation: The limits of detection (LODs, S / N=3), limits of quantitation (LOQs, S / N=10), linear range, and linear correlation coefficient R were examined. 2 And parameters such as precision. The results are shown in Table 1. The three NSAIDs showed good linearity in the range of 0.5-200 ng / mL, with a linear correlation coefficient R. 2 All values ​​were above 0.99. LODs ranged from 0.030 to 0.075 ng / mL, and LOQs ranged from 0.10 to 0.25 ng / mL. Intra-day precision (n=3) was 1.0-1.3%, inter-day precision (n=3) was 2.2-3.0%, and inter-batch precision (n=3) was less than 4.6%, indicating that the method has good repeatability.

[0069] Table 1. Methodological parameters for three NSAID analysis methods

[0070] 4. Validation of actual water samples: Mixed working solution was added to actual samples and spike recovery test was performed. The results are shown in Table 2. The spike recovery rate was in the range of 88.4-106.7%, and the RSDs were less than 5.97%, indicating that the method is highly accurate and can be used for reliable detection of nonsteroidal anti-inflammatory drug compounds in aquatic matrix.

[0071] Table 2. Detection results of NSAIDs in actual water samples

[0072] ND: Not detected.

[0073] 5. Reusability: This example also investigated the reusability of the Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material. For example... Figure 10 As shown, under the same extraction conditions, after 10 repeated uses, the enrichment efficiency of the Fe3O4@COF TAPT-TFA magnetic solid phase extraction material did not decrease significantly, indicating that the extraction material of the present invention has good reusability.

[0074] Comparative Example 2 The non-nitrogen-rich conventional Fe3O4@COF TAPB-TFP magnetic solid-phase extraction material prepared in Comparative Example 1 was applied to the enrichment and detection of trace nonsteroidal anti-inflammatory drug compounds in the aquatic environment according to the method in Example 2. The results are as follows: Figure 11 As shown, the non-nitrogen-rich Fe3O4@COF TAPB-TFP magnetic solid-phase extraction material prepared in Comparative Example 1 showed poorer detection performance for four non-steroidal anti-inflammatory drug compounds than the Fe3O4@COF TAPT-TFA prepared in Example 1. This indicates that the non-nitrogen-rich COF prepared in Comparative Example 1 has significantly lower enrichment and extraction performance for the four NSAIDs than the Fe3O4@COF TAPT-TFA prepared in Example 1. This result fully demonstrates that the high nitrogen content (triazine ring nitrogen and tertiary amine nitrogen) in the COF backbone can provide strong hydrogen bonding sites, acid-base interaction sites, and enhanced π-π stacking interactions, thereby synergistically improving the extraction selectivity and enrichment efficiency for NSAID molecules containing carboxyl groups and aromatic ring structures.

[0075] In summary, the method for detecting trace nonsteroidal anti-inflammatory drug compounds in the aquatic environment based on Fe3O4@COF TAPT-TFA magnetic solid-phase extraction material of this invention not only exhibits a good linear range, but also has high sensitivity, high accuracy and good repeatability, and can be used for high-precision detection of nonsteroidal anti-inflammatory drug compounds in the aquatic environment.

[0076] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

[0077] The embodiments described above are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various other corresponding changes and modifications based on the technical solutions and concepts described above, and all such changes and modifications should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing COF magnetic nanoparticle solid-phase microextraction materials, characterized in that, Magnetic nanoparticles Fe3O4 were synthesized by hydrothermal method using FeCl3•6H2O as the iron source under alkaline conditions. COF TAPT-TFA was then modified on the surface of the magnetic nanoparticles Fe3O4 using a solvothermal method to obtain solid-phase microextraction materials.

2. The preparation method according to claim 1, characterized in that, The preparation method of the magnetic nanoparticles Fe3O4 includes the following specific steps: ethylene glycol, anhydrous sodium acetate, sodium poly(4-styrenesulfonic acid-copoly-maleic acid) salt and FeCl3•6H2O are mixed to obtain a mixed solution; the mixed solution is reacted at 150-200℃ for 6-12h; after the reaction is completed, it is cooled to room temperature, the product is separated, and the product is washed and dried to obtain magnetic nanoparticles Fe3O4.

3. The preparation method according to claim 2, characterized in that, The molar ratio of FeCl3•6H2O to sodium poly(4-styrenesulfonic acid-copolymer-maleic acid) is 1:0.5-4; the molar ratio of FeCl3•6H2O to anhydrous sodium acetate is 1:8-20; and the addition ratio of FeCl3•6H2O to ethylene glycol is 0.4-0.6g:10-50mL.

4. The preparation method according to claim 1, characterized in that, The preparation method of the solid-phase microextraction material includes the following specific steps: 1,3,5-tris(4-aminophenyl)triazine, tris(4-formylphenyl)amine and the magnetic nanoparticles Fe3O4 are mixed, and then n-butanol, water and glacial acetic acid are added. The mixture is reacted at 60-80℃ for 14-18h. After the reaction is completed, the product is separated, washed and dried to obtain the solid-phase microextraction material.

5. The preparation method according to claim 4, characterized in that, The molar ratio of 1,3,5-tris(4-aminophenyl)triazine to tris(4-formylphenyl)amine is 1:1; the mass ratio of 1,3,5-tris(4-aminophenyl)triazine to magnetic nanoparticles Fe3O4 is 25-50:20-50; and the addition ratio of 1,3,5-tris(4-aminophenyl)triazine, n-butanol, water, and glacial acetic acid is 25-50 mg:0.5-2.5 mL:0.1-0.4 mL:0.2-0.8 mL.

6. A COF magnetic nanoparticle solid-phase microextraction material, characterized in that, It is prepared by any one of the preparation methods described in claims 1-5.

7. The application of the COF magnetic nanoparticle solid-phase microextraction material as described in claim 6 in the enrichment of trace nonsteroidal anti-inflammatory drug pollutants.

8. The application according to claim 7, characterized in that, The nonsteroidal anti-inflammatory drug contaminants include at least one of diclofenac sodium, naproxen, and ibuprofen.

9. A method for detecting nonsteroidal anti-inflammatory drug contaminants, characterized in that, The method includes the following steps: mixing the COF magnetic nanoparticle solid-phase microextraction material as described in claim 6 with the test solution to extract and enrich non-steroidal anti-inflammatory drug contaminants in the test solution; after extraction and enrichment, separating the COF magnetic nanoparticle solid-phase microextraction material, discarding the water sample, adding methanol and 0.1 M sodium hydroxide as eluent for elution, collecting the eluent after elution, and filtering the eluent through a filter membrane and detecting it by a high-performance liquid chromatography-diode array detector.

10. The method according to claim 9, characterized in that, The extraction and enrichment conditions include: an extraction and enrichment time of 5-30 min, a pH of 4-9, and an extraction material dosage of 0.25-2.0 mg COF magnetic nanoparticle solid-phase microextraction material per 4 mL of test solution; an elution time of 5-30 min; separation using a 200 mm × 2.1 mm, 1.9 µm C18 column, a flow rate of 0.3 mL / min, and an injection volume of 20 µL.